Magnetic Resonance Imaging in ADNI - Jack, Clifford R. (Alzheimers Dement, 2015)
INTRODUCTION: ADNI is now in its 10(th) year. The primary objective of the MRI core of ADNI has been to improve methods for clinical trials in Alzheimer’s disease and related disorders. METHODS: We review the contributions of the MRI core from present and past cycles of ADNI (ADNI 1, GO and 2). We also review plans for the future – ADNI 3. RESULTS: Contributions of the MRI core include creating standardized acquisition protocols and quality control methods; examining the effect of technical features of image acquisition and analysis on outcome metrics; deriving sample size estimates for future trials based on those outcomes; and piloting the potential utility of MR perfusion, diffusion, and functional connectivity measures in multicenter clinical trials. DISCUSSION: Over the past decade the MRI core of ADNI has fulfilled its mandate of improving methods for clinical trials in Alzheimer’s disease and will continue to do so in the future.